2015
DOI: 10.1177/1758573215573456
|View full text |Cite
|
Sign up to set email alerts
|

Cementless surface replacement hemiarthroplasty for primary glenohumeral osteoarthritis: results of over 5-year follow-up in patients with or without rotator cuff deficiency

Abstract: CSRHA provides significant improvements in pain and function in patients with glenohumeral osteoarthritis. In patients with deficient cuffs, functional gains are limited, and should be considered in low-demand patients where pain is the primary problem. Caution should be taken in patients with a deficient subscapularis as a result of the risk of dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Outcome scores for OA were lower than those from another study of CRHA for OA in 2012 which found postoperative OSS of 42 (versus 35 in this study) and Constant score of 62.5 (versus 49.9 in this study), although this was a small single surgeon series. 18 Functional outcomes for HA have not been proven superior to resurfacing with a recent study publishing a 5-year mean OSS of 32.7 19 although the Oxford group found the minimum 3-year (53.5 months mean follow-up) OSS of 38.8 for HA in OA with an intact rotator cuff. 20 A Danish randomized trial found similar CMS in OA patients treated with resurfacing hemiarthroplasty (48.9) to this study (49.9) although this was not using the CRHA prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome scores for OA were lower than those from another study of CRHA for OA in 2012 which found postoperative OSS of 42 (versus 35 in this study) and Constant score of 62.5 (versus 49.9 in this study), although this was a small single surgeon series. 18 Functional outcomes for HA have not been proven superior to resurfacing with a recent study publishing a 5-year mean OSS of 32.7 19 although the Oxford group found the minimum 3-year (53.5 months mean follow-up) OSS of 38.8 for HA in OA with an intact rotator cuff. 20 A Danish randomized trial found similar CMS in OA patients treated with resurfacing hemiarthroplasty (48.9) to this study (49.9) although this was not using the CRHA prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, RHA has been promoted as a bone-sparing alternative to SHA for over ten years among doctors and patients. Various types of resurfacing procedures have been described in terms of shortand mid-term clinical effectiveness by mounting studies [32,53,[57][58][59][60] and a recent systemic review [61] suggested that resurfacing replacements could provide a significant improvement in pain, motion, and standardized outcome scores.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it can also provide pain relief and avoid the glenoid loosening associated with TSA [ 22 ]. With continuous development and modification, HA has been applied for the treatment of various shoulder disorders, including the primary osteoarthritis (POA) [ 53 ], avascular necrosis (AVN) [ 16 ], rheumatoid arthritis (RA) [ 54 ], cuff-tear arthropathy (CTA) [ 18 ], juvenile idiopathic arthritis (JIA) [ 55 ] and post-traumatic degenerative joint disease (DJD) [ 56 ]. Especially, RHA has been promoted as a bone-sparing alternative to SHA for over ten years among doctors and patients.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Although HHR has been thought to preserve bone stock, permitting a later revision if needed, a loss of bone volume was noted below the HHR implant, 22 and revisions after HHR had lower Western Ontario Osteoarthritis of the Shoulder Index scores. 23 It has been proposed that HHR results in poor postoperative range of motion in those with preexisting rotator cuff injury, 24 although various studies have shown that pain relief, 20 functional improvement, patient satisfaction, 25 and improved range of motion were noted postoperatively. 20 , 26 A major limitation of current HHR literature is small sample sizes.…”
Section: Discussionmentioning
confidence: 99%